Association between Quality of life, Sleepiness, Fatigue, and Anthropometric Parameters in young University Students - Andrade,Rosane de Almeida (2020)
ABSTRACT Cardiovascular risks are now an epidemiological reality among adults and teenagers. This scenario leads to impairments in quality of life and represents a burden in healthcare and government costs. This study aimed to evaluate the association between risk factors for cardiovascular diseases, quality of life, daytime sleepiness, fatigue, and anthropometric parameters on university students in Fortaleza/CE, Brazil. It was a descriptive, crossectional, correlational study, made through epidemiological assessment in young university students, with primary data and quantitative analysis. The results showed a negative influence of daytime sleepiness and fatigue on the overall quality of life. Functional capacity, a component of the quality of life, which represents the ability to perform tasks and activities in their life, and limitations due to emotional aspects could impact a person's well-being and health. Moreover, excessive daytime sleepiness showed a strong correlation with almost all domains of quality of life. It was found that although volunteers did not show a low quality of life, fatigue levels and sleepiness presented as relevant variables. There is a need to comprehend and control these variables to promote students’ health and, consequently, to live healthier adulthood.